Learning Arabic in the Digital Era: Challenges and Effective Strategies - Rezkya Afril; Ilya Husna; Hasan Jasem (PPPBA, 2024)
The learning of Arabic language has undergone significant changes with the development of digital technology. This article aims to formulate the understanding of Arabic language learning in the digital era, explore challenges, and discover effective strategies to overcome them. This research utilizes the Library Research method with content analysis techniques. The research findings indicate that Arabic language learning in the digital era is a process of teaching and learning utilizing technology to enhance effectiveness and accessibility. Key challenges include digital divide, limited access to quality resources, the need for technology training for educators, and a lack of direct interaction with native speakers. Effective solutions include reducing the digital divide by improving internet access, providing quality digital resources, technology training for educators, and facilitating direct interaction with native speakers. Despite significant challenges, the potential to enhance the quality of Arabic language learning through digital innovation is substantial. With the right approach, Arabic language learning can become more effective, engaging, and inclusive in this digital era